Customer experience interaction and its role in organizational commitment : Analytical research for the opinions of a sample of workers in Noor Al-Kafeel Company - Qassem Al-Khafaji, Yasmine (Iraqi Journal for Administrative Sciences, 2024)
The current research aims to know the relationship between customer experience interaction and its role in organizational commitment in (Noor Al Kafeel Company). A significant effect of customer experience interaction on organizational commitment, and accordingly, the research found many Conclusions and recommendations, the most important of which is that Noor Al-Kafeel Company cares about interacting with customers’ experience and works to achieve what they desire from products that suit all tastes, and provides a high organizational commitment for employees, which is reflected on their job satisfaction and creativity at work. They want new products that meet their needs and desires, which increases the company's productivity and achieves a sustainable competitive advantage.